Have the Annual Trends of Total Knee Arthroplasty in Rheumatoid Arthritis Patients Changed? - Harb, Matthew A.; Solow, Max; Newman, Jared M.; Sodhi, Nipun; Pivec, Robert; George, Jaiben; Sultan, Assem A.; Khlopas, Anton; Shah, Neil V.; Roche, Martin W.; Mont, Michael A. (The Journal of Knee Surgery, 2018)
As the use of disease modifying antirheumatic drugs have increased, it remains unclear whether or not this has affected the rates of total knee arthroplasty (TKA) in rheumatoid arthritis (RA) patients. Therefore, the purpose of this study was to evaluate the annual trends of RA patients who underwent TKA. Specifically, we evaluated: (1) the annual trends of TKAs due to RA in the United States population; and (2) the annual trends in the proportion of TKAs due to RA in the United States. The Nationwide Inpatient Sample was used to identify all patients who underwent TKA between 2002 and 2013 (n = 6,492,873). Then, we identified TKA patients who had a diagnosis of RA, defined by the International Classification of Diseases, Ninth Revision (ICD-9) code 714.0. The incidence of TKAs with a diagnosis of RA in the United States was calculated using the U.S. population as the denominator. Regression models were used to analyze the annual trends of RA in patients who underwent TKA. A total of 209,332 RA patients were identified who underwent TKA. The annual prevalence of RA in patients who underwent TKA slightly increased, from 33.2 per 1,000 TKAs in 2002 to 35 per 1,000 TKAs in 2013 (R2 = 0.254, p = 0.095). The annual number of TKAs with a diagnosis of RA increased by 93.1% from 11,618 to 22,430. After normalizing for the U.S. population, the incidence of TKAs with RA increased from 5.4 to 9.2 TKAs per 1 million U.S. adults (incidence rate ratio [IRR] = 1.05; 95% confidence interval [CI], 1.05–1.05; p < 0.001). In 2002, 11,618 (3.31%) TKAs, and in 2013, 22,430 (3.50%) TKAs were due to RA. The prevalence of RA in those who underwent TKA remained the same from 2002 to 2013 (coefficient = 0.02; 95% CI, –0.01 to 0.05; p = 0.095). The results of this study demonstrated that the rates of TKA performed in RA patients have remained relatively stable. Furthermore, there may have been a decline in the rate of RA patients undergoing TKA, due to an increase in the U.S. population by approximately 28.8 million during the study period.
Keywords: total knee arthroplasty; rheumatoid arthritis; annual trends